The Phytochemical Shikonin Stimulates Epithelial-Mesenchymal Transition (EMT) in Skin Wound Healing. (3rd June 2013) - Yin, Shu-Yi; Peng, An-Ping; Huang, Li-Ting; Wang, Ya-Ting; Lan, Chun-Wen; Yang, Ning-Sun
Abstract : Although various pharmacological activities of the shikonins have been documented, understanding the hierarchical regulation of these diverse bioactivities at the genome level is unsubstantiated. In this study, through cross examination between transcriptome and microRNA array analyses, we predicted that topical treatment of shikonin in vivo affects epithelial-mesenchymal transition (EMT) and the expression of related microRNAs, including 200a, 200b, 200c, 141, 205, and 429 microRNAs, in mouse skin tissues. In situ immunohistological analyses further demonstrated that specific EMT regulatory molecules are enhanced in shikonin-treated epidermal tissues. RT-PCR analyses subsequently confirmed that shikonin treatment downregulated expression of microRNA-205 and other members of the 200 family microRNAs. Further, expression of two RNA targets of the 200 family microRNAs in EMT regulation, Sip1 (Zeb2) and Tcf8 (Zeb1), was consistently upregulated by shikonin treatment. Enhancement of these EMT activities was also detected in shikonin-treated wounds, which repaired faster than controls. These results suggest that topical treatment with shikonin can confer a potent stimulatory effect on EMT and suppress the expression of the associated microRNAs in skin wound healing. Collectively, these cellular and molecular data provide further evidence in support of our previous findings on the specific pharmacological effects of shikonin in wound healing and immune modulation.